Formation of a crop of medicinal crops (Tanacetum vulgare L., Echinacea purpurea L.) under influence of essential microelements - Natalya N. Zharkova; Valentina V. Sukhotskaya; Yuri I. Ermokhin (Овощи России, 2019)
Relevance. A wide range of pharmacological effects of tansy and Echinacea purpurea determine the continuing interest in the study of these cultures. Medicinal crops contain not only a large number of biologically active substances, but also trace elements necessary for normal growth and development. Agronomic bio-enrichment of medicinal raw materials allows you to increase productivity, manage product quality in the direction of enhancing the pharmacological action. Thus, the aim of the work was to study the effect of various doses of zinc acetate on the productivity of two medicinal crops of tansy and Echinacea purpurea.Material and methods. Studies were conducted from 2012 to 2018 on meadow-chernozem soil of the southern forest-steppe of Western Siberia. As objects of research, perennial medicinal crops were chosen – Tanacetum vulgare L. and Echinacea purpurea L. Zinc fertilizers were applied in the background (N125, N135P45K45) used in acetate form.Results. The introduction of zinc fertilizers into the soil contributed to an increase in the yield of medicinal crops in the conditions of the south of Western Siberia. It was revealed that the maximum yield was observed on the variants of 0.75 MAC Zn (Tanacetum vulgare L.) and 0.5 MAC Zn (Echinacea purpurea). Thus, tansy was more responsive to the use of micronutrient fertilizers. The studies established a high correlation relationship (r = 0.88–0.99) between yield indicators and doses of zinc added. The obtained optimal doses of zinc fertilizers (60 and 21.4 kg / ha) can be recommended for growing these crops in order to increase their productivity.